Caracterização dos parâmetros acústicos do golfinho-rotador: registro na quebra da plataforma continental sul Brasileira - Moron, Juliana Rodrigues (Universidade Federal de Juiz de Fora, 2015)
Spinner dolphins’ bioacoustics have already been described in literature, meanwhile the Western South Atlantic Ocean was only approached inside Fernando de Noronha Archipelago. Therefore, in order to contribute to a better knowledge of this cosmopolitan species, this study aimed to describe the sounds through their acoustic parameters detected during an opportunistic recording carried out at the Brazilian continental shelf break. A group of approximate 400 Stenella longirostris dolphins was recorded through a one-element hydrophone array performing continuous mono recording at 96 kHz/24 bits. After a 12 minutes selection of the record, 1,100 whistles were extracted and classified into seven contours shapes, along with other ten variables extracted. The spinner dolphins whistles was mostly comprised by upsweep (41.2%) contour. The group produced higher pitch frequency modulated whistles than what has been previously described, presenting a maximum frequency of 26.4 kHz. Despite the short whistle durations, ranging from 0.03 s to 2.56 s (mean = 0.67 s), those values were also higher than most of previous works had reported. Despite statistically significant differences, the comparison from the average of the extracted parameters pointed out that two previous studies in the North Pacific Ocean are more similar in relation to this study. Thereby, the possibilities from the comparisons discussed in this paper not only assist in identifying the variability in the emissions in order to improve acoustic detection classifications in research and impact mitigation; but also contribute to the understanding of distinct populations and/or species distributed in different ocean basins. Apesar de investigações bioacústicas de golfinhos-rotadores já terem sido abordadas e descritas na literatura, a região do Oceano Atlântico Sul Ocidental só abrangeu a população do arquipélago de Fernando de Noronha. Portanto, a fim de contribuir para um melhor conhecimento desta espécie cosmopolita, este estudo teve como objetivo descrever ...